J/ψ Suppression at Forward Rapidity in Pb-Pb Collisions at √sNN=2.76 TeV - Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agocs, A. G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Masoodi, A. Ahmad; Ahmad, N.; et al. (AMER PHYSICAL SOC, 2012)
The ALICE experiment has measured the inclusive J/psi production in Pb-Pb collisions at root s(NN) = 2.76 TeV down to zero transverse momentum in the rapidity range 2.5 < y < 4. A suppression of the inclusive J/psi yield in Pb-Pb is observed with respect to the one measured in pp collisions scaled by the number of binary nucleon-nucleon collisions. The nuclear modification factor, integrated over the 0%-80% most central collisions, is 0.545 +/- 0.032(stat) +/- 0.083dsyst_ and does not exhibit a significant dependence on the collision centrality. These features appear significantly different from measurements at lower collision energies. Models including J/psi production from charm quarks in a deconfined partonic phase can describe our data.
Keywords: Physics